Perbandingan Rumah Joglo di Jawa Tengah Dalam Lingkup Cagar Budaya (Studi Kasus: Omah UGM dengan nDalem Purwodiningratan)( - Anugrah Pratama; Yusuf Affendi Djalari; Sangayu Ketut Laksemi (Jurnal Seni dan Reka Rancang: Jurnal Ilmiah Magister Desain, 2018)
AbstractJoglo house has a deep meaning and represent Javanese identity. The structure of Joglo’s building for Javanese people is in accordance with the principle of Javanese people’s life, to firmly taking the responsibility of living. In the past, this building was become a symbolic of middle-upper class status in society and destined for living place, cultural art show, assembly hall, and ceremonial events. As the time goes by, there is a change of building function, building construction and ownership. Therefore, there is a need of special attention from government related to the preservation of ancient and historical buildings in accordance with Law No.11 year 2010 regarding cultural heritage. The preservation may include historical building conservation (preservation, restoration, reconstruction and revitalization). Conservation is often to accompanied by the development of design construction, which can give an impact to the change of meaning or identity and function of Joglo house. The switches of function of Joglo house was identified by the author through the case study of Joglo houses in Kotagede Heritage, Yogyakarta and Solo, Surakarta. Joglo house in Kotagede which has been observed by the author was Omah UGM.Meanwhile, Joglo house in Solo, Surakarta was nDalem Purwodiningratan. The development of both Joglo houses was observed in the terms of function, and the shape of building. As a result, the author conclude that both of the Joglo houses have the historical value that deserve to be categorized as cultural heritage and needs to be preserved.AbstrakRumah Joglo memiliki makna dan identitas yang kuat bagi masyarakat jawa. Struktur bangunan rumah Joglo bagi masyarakat jawa sesuai dengan prinsip kehidupan masyarakatnya yaitu tegas dalam menjalani tanggung jawab dalam kehidupan. Di masa lalu, bangunan sebagai simbol status kelas masyarakat menegah ke atas ini diperuntukkan untuk tempat tinggal, kegiatan pementasan, ruang pertemuan, dan acara seremonial. Seiring dengan perkembangan zaman, terjadi perubahan fungsi, konstruksi bangunan serta kepemilikan, sehingga makna dan filosofi rumah Joglo berkurang. Oleh karena itu, diperlukan perhatian khusus dari pemerintah terkait pelestarian bangunan kuno dan bersejarah sesuai dengan UU No. 11 tahun 2010 tentang cagar budaya. Pelestarian ini dapat berupa konservasi bangunan bersejarah (preservasi, restorasi, rekonstruksi maupun revitalisasi). Konservasi seringkali disertai dengan adanya pengembangan kontruksi desain yang dapat berdampak pada perubahan makna/identitas maupun fungsi dari rumah Joglo. Rumah Joglo yang beralih fungsi ini penulis mengidentifikasi melalui studi kasus bangunan rumah Joglo yang berada pada kawasan cagar budaya Kota Gede di Yogyakarta dan Solo, Surakarta. Rumah Joglo di Kota Gede yang diamati penulis adalah Omah UGM